Application of Couple Card Media With Make A Match Learning Model in Improving Students' Collaboration Skills at SMA Negeri 9 Surabaya - Widjanarko, Kartika Irene; Agung Pranoto (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
The skill of working together is essential for students in the 21st century. However, many students still lack adequate collaboration skills, necessitating a learning method supported by educational media to enhance these skills. This classroom action research seeks to enhance students' collaboration skill at SMA Negeri 9 Surabaya through the use of Couple Card’s media with Make a Match learning learning model. The research involves two steps consisting of four stages: there are plan, implementation, observation, and reflection. The subjects of the study are 34 students from class X-9 at SMA Negeri 9 Surabaya. The Data collection techniques are include observation and interviews, with data analyzed descriptively and presented in tables and charts. The results show that the use of Couple Card media with the Make a Match learning model in the second cycle significantly improved students' collaboration skills. Additionally, students were actively engaged and showed interest in the learning process. Overall, this study demonstrates that the use of Couple Card media is effective in enhancing students' collaboration skills.